170k views
2 votes
Simplify.-2V/24y2 + 5V 96y?

1 Answer

6 votes

The first step is to simplify the terms containing square roots. Thus, we have


\begin{gathered} \sqrt[]{24y^2}\text{ = 2y}\sqrt[]{6} \\ \text{Thus, } \\ -\text{ 2}\sqrt[]{24y^2}\text{ = - 2 }*2\sqrt[]{6} \\ =\text{ - 4}\sqrt[]{6} \\ \text{Also, } \\ \sqrt[]{96y^2}\text{ = 4y}\sqrt[]{6} \\ \text{Thus, } \\ 5\sqrt[]{96y^2}^{}\text{ = 5 }*4y\sqrt[]{6} \\ =\text{ 20y}\sqrt[]{6} \\ We\text{ would add both terms. Thus, we have} \\ -\text{ 4y}\sqrt[]{6}\text{ + 20y}\sqrt[]{6} \\ =\text{ 16y}\sqrt[]{6} \end{gathered}

We expressed both terms in surd form. The square root

User Adnan Rasheed
by
5.0k points